Performans Reproduksi Sapi Peranakan Simmental (Psm) Hasil Inseminasi Buatan di Kabupaten Sukoharjo Jawa Tengah - Iswoyo, Iswoyo; Widiyaningrum, Priyantini (Fakultas Peternakan Universitas Jambi, 2008)
Information of performance reproduction crossed result of cow in ranch was immeasurable enough because condition of its different conservancy. This research aimed to know difference of reproduction performances of Simmental Crossed Cow (PSM) result of Artificial Insemination (AI) looked after by farmer of breeder of Group Farmer Livestock member (KTT) and non member of KTT in District of Sukoharjo. Research conducted with method of survey by means of questionaire. Determination of research sample arranged purposive sampling. Variables were perceived to cover pregnant time depth, service period, calving interval, non return rate and service per conception. Data had been analyzed with Z test or presented descriptively. Results of this research indicated that difference of breeder status (member of KTT and non KTT) giving different influence in conservancy. Statistical analysis result of research successively indicated that gestation period mean of PSM cow property of member of KTT and non member of KTT did not differ reality (KTT 301.82 ± 29.93 day; non KTT 308.5 ± 33.73 day); service period differ reality (KTT 110.89 ± 30.23 day; non KTT 114.11 ± 56.78 day). Calving interval differ reality (KTT 392.28 ± 77.27 day, non KTT 416.02 ± 64.63 day); non return rate differ reality (KTT 87.72 ± 11%; non KTT 79.53 ± 18%); service per conception do not differ reality (KTT 1.12 ± 0.32; non KTT 1.19 ± 0.40. This research concluded that performance reproduction of PSM cow looked after by breeder of member of KTT better in general compared to cow of PSM looked after by is breeder non KTT